Outcomes of epiretinal membrane surgery in highly myopic eyes: a case–control study. Issue 6 (19th December 2014) - Conart, Jean-Baptiste; Favel, Constance; Selton, Jérôme; Hubert, Isabelle; Cloche, Véronique; Trechot, Fanny; Berrod, Jean-Paul
Abstract : Aims: To evaluate the outcomes of epiretinal membrane (ERM) surgery in highly myopic eyes and to compare them with those from non-highly myopic eyes. Methods: Retrospective nested case–control study from a cohort of 1776 consecutive patients (1776 eyes) who underwent surgery for ERM. Fifty-seven highly myopic eyes (with axial length longer than 26 mm) were included in the study group and were matched for preoperative visual acuity and duration of symptoms with 57 non-highly myopic control eyes selected from the same cohort. The best-corrected visual acuity (BCVA), the relationship between axial length and visual improvement, the central macular thickness (CMT) and the surgical complications were analysed. Results: The mean axial length was 27.3±1.1 mm in highly myopic eyes and 23.1±1 mm in controls (p<0.001). At the 1-year final examination, the mean BCVA significantly improved from 0.62±0.23 logarithm of minimal angle of resolution (logMAR) to 0.27±0.21 logMAR in the study group (p<0.001) and from 0.61±0.22 logMAR to 0.25±0.15 logMAR in the control group (p<0.001). Similarly, the mean CMT significantly decreased in both groups (p<0.001). The two groups did not differ statistically in terms of visual and anatomical changes as well as surgical complications. There was no significant correlation between axial length and visual recovery. Conclusions: ERM surgery resulted in similar anatomical and functional outcomes in both groups. Longer axial length does not seem to affect visual improvement and the complication rate.